Implementation of "Mitis iudex Dominus Iesus" in the Diocese of Springfield in Illinois - Paprocki, Thomas John (The jurist, 2015)
The diocesan bishop should promulgate his decisions regarding the implementation of the motu proprio Mitis iudex Dominus Iesus by issuing a general executory decree, which according to canon 31 serves "to determine more precisely the methods to be observed in applying the law." In his the revision of the canonical process for the declaration of the nullity of marriage in the Code of Canon Law, Pope Francis has not only taken steps to make these processes more readily available to those in need of the judicial function of the Church, but has also called for diocesan bishops themselves to be more personally involved in the exercise of their judicial power of governance as described in canon 391. In this way, diocesan bishops more fully exercise their threefold munera to teach, govern and sanctify the People of God entrusted to them as successors of the apostles by divine institution. Bishop Paprocki of the Diocese of Springfield in Illinois explains how he implements Mitis iudex in his diocese.